Christian Theology in Asia - Sebastian C. H. Kim (Cambridge Cambridge University Press, 2008)
The majority of the world's Christians now live outside Europe and North America, and global Christianity is becoming increasingly diverse. Interest in the history and theology of churches in non-Western contexts is growing rapidly as 'old world' churches
Keywords: Theology - Asian. Theology -- Asia. Asia -- Church history. RELIGION -- Christianity -- General. RELIGION -- Christian Theology -- Systematic. Theology. Asia. Christentum Theologie Asien